Health-related quality of life as measured with the Short-Form 36 (SF-36) questionnaire in patients with recurrent vulvovaginal candidiasis - Zhu, Yu-Xia (Health Qual Life Outcomes, 2016)
BACKGROUND: Recurrent vulvovaginal candidiasis (RVVC) has a poor therapeutic outcome and a severe impact on women and their partners, both physically and psychologically. Health-related quality of life (HRQOL) is significantly affected in patients with RVVC; however, little is known about HRQOL in patients with this disease. In this study, we aim to identify the clinical and mycological characteristics of women with RVVC and the effects of RVVC on women’s HRQOL. METHODS: We designed this study as a comparative cross-sectional study. The Short-Form Health Survey (SF-36) was used to measure HRQOL in 102 patients with RVVC and 101 women seeking general health care (controls). RVVC was defined as four or more episodes of proven VVC in the previous 12-month period. VVC was defined as vulvar itching, burning, erythema, vaginal discharge, pseudohyphae or blastoconidia on a wet 10 % potassium hydroxide (KOH)-treated vaginal slide and a positive Candida culture. Group comparisons were conducted with independent samples t test. Correlation analysis was performed on the variables. RESULTS: The mean age at first diagnosis of the patients with RVVC was 30.96 years (SD 5.38), and the mean age of the controls was 29.75 years (SD 5.83; p > 0.05). The duration of the patients’ complaints varied from 6 months to 10 years, with a mean duration of 22.28 (±21.75) months. The most common complaints were increased vaginal discharge (102 cases, 100 %), itching (97 cases, 95.1 %), dyspareunia (65 cases, 63.7 %), burning (79 cases, 77.5 %) and erythema (25 cases, 24.5 %). C. albicans was the predominant Candida species (86 strains, 84.3 %) in the patients, followed by C. glabrata (12 strains, 11.8 %). C. parapsilosis (1 strain, 0.9 %), C. tropicalis (1 strain, 0.9 %), C. krusei (1 strain, 0.9 %) and C. lusitaniae (1 strain, 0.9 %). The mean SF-36 dimension scores for physical function, role physical, bodily pain, general health, vitality, social functioning, role emotional, and mental health were significantly lower in the patients with RVVC than in the controls (85.20, 61.39, 77.79, 54.95, 53.17, 67.89, 52.48 and 59.17 vs. 90.20, 80.87, 87.08, 67.38, 59.69, 79.86, 68.01 and 65.38). The physical composite and mental composite scores of the patients with RVVC were 63.06 and 64.87, respectively, which were lower than those of the controls (75.01 and 74.87; p < 0.05). CONCLUSIONS: Nearly all of the patients with RVVC had clinical symptoms. In our sample, RVVC was mainly caused by C. albicans. RVVC has negative effects on women’s HRQOL, as indicated by lower physical and mental composite scores among the RVVC group compared with controls.